Politisasi Birokrasi: Pola Hubungan Politik dan Birokrasi di Indonesia - Yudiatmaja, Wayu Eko (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2015)
Pola Hubungan Politik dan Birokrasi di Indonesia   Wayu Eko Yudiatmaja(wayuguci@gmail.com) (Jurusan Ilmu Administrasi Negara FISIP UMRAH)   Abstract: This paper highlights the politization of bureaucracy in Indonesia. The purpose of this study is to explain the practices of politization in Indonesian bureaucracy. The qualitative approach is used to explore it purpose. The data of this study are gained from the secondary sources. Finding of this research conclude that the politization ensuethroughout Indonesian voyage. Further, the politization will be discussed in three periods, included pre-colonial, colonial, Old Order, New Order, and post New Order.The politization of bureaucracy are determined by liberal democracy, multi-party system, and high-cost politics.